(untitled) (Research, Society and Development, 2021)
Objective: recognize and analyze cases of dentistry error against dentists, exercising public function. Methodology: decision research on the sites of the Courts of Justice of Minas Gerais, Amazonas, Ceará, Rio de Janeiro, Santa Catarina and the Federal District in the period between 2014 and 2019 based on the proposed script. Results: There was a small number of demands against dentists in the exercise of functions within the public service, in the courts of justice studied. A total of 10 processes were identified, namely: 2 in Minas Gerais, 0 in Amazonas, 2 in Ceará, 2 in Rio de Janeiro, 3 in Santa Catarina and 2in the Federal District. As for the variables analyzed: 100% received free legal assistance; only the public entity was sued; when the data was found, objective responsibility was assigned to the respondent; there was a predominance of joint material/moral damage; there was an unfavorable decision to the public entity in most cases and the most frequent procedures were surgery. Conclusion: Despite the small number of cases found, the study can be considered preliminary for a deeper analysis of public responsibility in the provision of dental services as a way to understand how the phenomenon of patient complaints occurs in the Unified Health System, which will allow preventive and corrective measures can be taken.